2012
DOI: 10.1155/2012/375148
|View full text |Cite
|
Sign up to set email alerts
|

From Spinal Central Pattern Generators to Cortical Network: Integrated BCI for Walking Rehabilitation

Abstract: Success in locomotor rehabilitation programs can be improved with the use of brain-computer interfaces (BCIs). Although a wealth of research has demonstrated that locomotion is largely controlled by spinal mechanisms, the brain is of utmost importance in monitoring locomotor patterns and therefore contains information regarding central pattern generation functioning. In addition, there is also a tight coordination between the upper and lower limbs, which can also be useful in controlling locomotion. The curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
80
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(89 citation statements)
references
References 60 publications
7
80
0
2
Order By: Relevance
“…Estos dispositivos permiten a los usuarios recuperar el uso de la extremidad perdida y volver a interaccionar con el entorno. Así mismo, la aplicación de esta tecnología en procesos de rehabilitación agiliza los procedimientos de recuperación [7], [8].…”
Section: Configuraciónunclassified
“…Estos dispositivos permiten a los usuarios recuperar el uso de la extremidad perdida y volver a interaccionar con el entorno. Así mismo, la aplicación de esta tecnología en procesos de rehabilitación agiliza los procedimientos de recuperación [7], [8].…”
Section: Configuraciónunclassified
“…Nicolelis demonstrated the EEG-controlled exoskeleton built by Gordon Cheng at the opening of World Football Cup in 2014. A similar project, the Mindwalker, emerged in Europe [58]. In parallel, Contreras Vidal and his colleagues proposed an idea of developing a leg exoskeleton controlled by slow EEG rhythms; in 2012 they decoded gait kinematics of a human walking on the treadmill [59].…”
Section: Bcis For Bipedal Locomotionmentioning
confidence: 99%
“…EEG results also showed changes in event-related synchronizations and desynchronizations over the 5 month period of the study that suggested cortical plasticity. The possibility of BCI in conjunction with virtual reality as a therapeutic regimen has also been discussed for walking rehabilitation and treatment of autism [102,103].…”
Section: Eeg-based Approachmentioning
confidence: 99%